2007
DOI: 10.2478/s11756-007-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

Paclobutrazol delayed dark-induced senescence of mung bean leaves

Abstract: Sixty days old mung beans Vigna radiata (L.) Wilczek were treated with soil applied paclobutrazol, at the rate of 500 µg per 10 inch pot. After seven days of application, the plants along with untreated controls were transferred to the dark for induction of senescence. The treated plants exhibited higher chlorophyll content and activity of catalase (CAT) compared to controls. In contrast, control leaves had higher activity of peroxidase (POX) and a higher content of malondialdehyde (MDA), while superoxide dism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
3
2
0
2
Order By: Relevance
“…PBZ application resulted in a significant reduction of peony plant height, irrespective of growth conditions (Table 1). This was in line with previous published reports [21]. PBZ application also decreased stem width in all tested conditions (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…PBZ application resulted in a significant reduction of peony plant height, irrespective of growth conditions (Table 1). This was in line with previous published reports [21]. PBZ application also decreased stem width in all tested conditions (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…Paclobutrazol application treatments, however, maintained significantly higher photosynthetic rates during both growing seasons, with the best effects observed in PS2 treatment compared to control and other paclobutrazol treatments. The increase in photosynthetic efficiency with paclobutrazol could be linked with the enhanced chlorophyll pigments and delayed leaf senescence at later growth stages in the treated maize plants, which is in agreement with the previous reports of Gopi et al [39], Bora et al [44], and Wang et al [45]. In support of our findings, previous studies have indicated that exogenous application of various triazole PGRs significantly improved the net photosynthetic rate in Raphanus sativus [46], Amorphophallus campanulatus [47], and Catharanthus roseus [48].…”
Section: Discussionsupporting
confidence: 93%
“…Судя по данным, полученным по восстановлению 2,3,5-трифенилтетразолий хлорида (ТТХ), в клетках колеоптилей, несмотря на значительное ингибирование роста, препарат не снижал жизнеспособность клеток исследуемых злаков, наоборот, с повышением его концентрации (с рекомендуемой 0,5 мкл/г до 5 мкл/г) степень восстановления ТТХ возрастала [32]. Вероятно, обладая ретардантными свойствами, тебуконазолсодержащий протравитель не только замедляет процессы роста, но и отодвигает сроки естественного старения клеток колеоптиля, что согласуется с данными, имеющимися в литературе о влиянии ретардантов триазольной природы (паклобутразола) на растения [16].…”
Section: физико-химическая биология / Physicochemical Biologyunclassified
“…Системные фунгициды и протравители семян, как отмечено в ряде публикаций, кроме сво- его основного назначения -проявлять фунгицидную активность у растений, вызывают еще ряд сопутствующих эффектов, которые отражаются на их урожайности [4][5][6][7][8][9]. Среди этих эффектов можно выделить следующие: ретардантное действие, обусловленное подавлением биосинтеза гиббереллина [10-13]; проявление эффекта зеленения растений вследствие увеличения содержания хлорофилла [14-18]; повышение содержания белка в зерне [9]; повышение устойчивости растений к различным стрессам (низким и высоким неблагоприятным температурам, водному дефициту и засухе, избыточному увлажнению, хлоридному засолению, УФ-В радиации, окислительному стрессу) [14,16,[19][20][21][22][23][24][25][26][27][28][29]; влияние на другие физиологобиохимические процессы растений [7,[29][30][31][32][33][34][35][36].…”
unclassified